Substituted phenyl urea and thiourea silatranes: Synthesis, characterization and anion recognition properties by photophysical and theoretical studies. (7th July 2016) - Singh, Gurjaspreet; Saroa, Amandeep; Rani, Sunita; Promila,; Girdhar, Shally; Sahoo, Subash; Choquesillo-Lazarte, Duane
Graphical abstract: An unsymmetrically substituted urea and thiourea possessing silatranes3 –8 were synthesized in good yield by the rearrangement reaction of phenyl isocyanates/isothiocyanates with 3-aminopropylsilatranes. All the compounds were characterized by elemental analysis, spectroscopic techniques and X-ray diffraction analysis in the case of3, 6 and8 . The electronic properties were studied by UV–Vis absorption and fluorescence emission spectra and correlated with quantum mechanical calculations. Abstract: A series of functionalized phenyl unsymmetrical urea and thiourea possessing silatranes3 –8 were synthesized in good yields by the rearrangement reaction of electrophiles 1-isocyanato-4-nitrobenzene, 1-isothiocyanato-4-nitrobenzene, 1-isocyanato-4-methoxybenzene, 1-isothiocyanato-4-methoxybenzene, 1-isothiocyanatobenzene with primary amines 3-aminopropylsilatrane1 and 3, 7, 10-trimethyl substituted 3-aminopropylsilatrane2 acting as nucleophiles. All the compounds were characterized by elemental analysis, spectroscopic techniques and X-ray diffraction analysis in the case of3, 6 and8 . The functionalized phenyl unsymmetrical urea and thiourea possessing silatranes3 –8 are categorized into three sub series depending upon the electron withdrawing or releasing effect of the groups attached to the silatrane's axial position and based on these observations, we describe the effect of each category on the electronic properties via solution state studies i.e. photophysical studies (UV–Vis absorption and fluorescence emission spectra). The geometries of all the compounds are optimized at the DFT/6-31+G(d) level using quantum mechanical calculations for supporting the photophysical studies.